Renewing Christian Witness in Europe—A Proposal - Christophe Chalamet (Religions, 2023)
The transmission of the Christian faith is severely broken in many western European countries. This does not bode well for the future of Christianity in these regions. In the face of this situation, Christians might be tempted either to “retreat” from the world and foster sectarian communities or to more or less completely “merge” with contemporary society. Both of these options are erroneous and amount to a distortion of what a genuine Christian witness might look like in the coming decades. The present essay attempts to draw some of the contours of what such a Christian witness may look like.